Experience of Stepwise Introduction of English Oak (Quercus robur L.) in Northern Latitudes - Aleksandr A. Karbasnikov; Elena B. Karbasnikova; Olga S. Zalyvskaya; Vladimir I. Melekhov (Лесной журнал)
The problem of enriching the dendroflora of green plantations in northern cities and their green zones with new species at the expense of introduced species is urgent. This problem can be solved by stepwise introduction, which is currently theoretically justified and has been repeatedly applied in practice. Climate warming makes it possible to consider nemoral dendroflora, in particular English oak, as promising for the European North. This species is highly decorative and has special ecosystem properties. In the southern taiga subzone, it occurs fragmentarily in floodplain forests, which has made it widespread in the landscaping of northern cities. It is the plantations of this species that should be considered primarily as a source of seed material. The aim of the study is to generalize the experience of stepwise introduction of English oak under the conditions of the northern agglomeration. The object of the study has become the city garden of Vologda, where at the beginning of the 20th century there has been a botanical garden with an exposition of broad-leaved forests. These plantations have been considered as the 1st stage of introduction. The 2nd stage has included plantations in the suburban green zone, created by seedlings created from seeds collected from trees of the city garden. The results of the comparative analysis have shown that the content of photosynthetic pigments, quantitative and qualitative characteristics of acorns of green zone trees are higher than those of city garden trees. It can be concluded that at both sites the plants retain their vital form and freeze slightly. The amount of photosynthetic pigments is within the normal range. The carotenoid content is at a high level, which ensures the resistance of trees to adverse climatic factors. The biometric parameters of the seeds correspond to the values typical for the natural growing conditions of the species. At the same time, it should be noted that according to some criteria, the trees in the green zone of the agglomeration are superior to those in the city limits. The high quality of the seed material allows us to recommend the use of green zone trees as mother trees. To obtain planting material, acorns of medium and large fractions should be used.